Spin‐Polarized Semiconductors: Tuning the Electronic Structure of Graphene by Introducing a Regular Pattern of sp3 Carbons on the Graphene Plane. Issue 2 (2nd October 2012) - Jing, Long; Huang, Ping; Zhu, Huarui; Gao, Xueyun
Abstract First‐principles calculations (generalized gradient approximation, density functional therory (DFT) with dispersion corrections, and DFT plus local atomic potential) are carried out on the stability and electronic structures of superlattice configurations of nitrophenyl diazonium functionalized graphene with different coverage. In the calculations, the stabilities of these structures are strengthened significantly since van der Waals interactions between nitrophenyl groups are taken into account. Furthermore, spin‐polarized and wider‐bandgap electronic structures are obtained when the nitrophenyl groups break the sublattice symmetry of the graphene. The unpaired quasi‐localized p electrons are responsible for this itinerant magnetism. The results provide a novel approach to tune graphene's electronic structures as well as to form ferromagnetic semiconductive graphene.